Analisis Perbandingan Algoritma NGG dan GGHN pada Frekuensi Hasil Enkripsi - Siregar, Farid Akbar; Rizka, Ade; Siregar, Annisa Fadillah (Building of Informatics, Technology and Science (BITS), 2022)
Data and information in the development of digital technology have an important role. Every activity or activity that uses digital technology is related to data and information, so information security and data confidentiality are very important. To maintain information security and data confidentiality, protection with cryptographic techniques is needed. Cryptographic techniques are related to encryption, which is where the process of scrambling data is carried out and hiding data with a key system, while decryption is the process of changing the condition of the data to its original form so that it is easy to understand. There are obstacles and problems ini digital communication, so cryptographic techniques are needed that have higher level of security and can be applied in digital communications. To determine the level of security in cryptographic techniques required frequency anlysis. Frequency analysis on the NGG and GGHN algorithms is carried out to determine the level of information security based on the results of data encryption. BAse on the testing process on the NGG and GGHN algorithms, it will be known that the frequency of characters in the text varies. The more characters used in the key will affect the level of information security. The NGG algorithm has a higher level of security than the GGHN algorithm with a precentage difference of 0.000299967%. If the frequency of occurrence of characters in the message text that has been encrypted is more frequent or higher, then the level of information security in the message is lower and the password is easier to crack.